2018
DOI: 10.1021/acs.est.7b04992
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Dependence of Nitrogen and Phosphorus as Key Nutrient Elements: One Facilitates Dolichospermum flos-aquae to Overcome the Limitations of the Other

Abstract: Dolichospermum flos-aquae (formerly Anabaena flos-aquae) is a diazotrophic cyanobacterium causing harmful blooms worldwide, which is partly attributed to its capacity to compete for nitrogen (N) and phosphorus (P). Preventing the blooms by reducing P alone or both N and P has caused debate. To test the effects alone and together on the growth of cyanobacteria, we performed culture experiments in different eutrophication scenarios. N fixation in terms of heterocyst density, nitrogenase activity and nifH express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 50 publications
4
25
0
5
Order By: Relevance
“…Previous studies have attempted to demonstrate the effect of N limitation on N fixation and heterocyst development in cyanobacteria via continuous culture by regulating the levels of combined N or nitrate alone. [ 8 , 27 , 28 , 29 ]. Enhanced development of heterocyst and nitrogenase activity under low levels of combined N or nitrate alone indicated that N fixation by heterocystous cyanobacteria was critical when available N source was limited or absent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to demonstrate the effect of N limitation on N fixation and heterocyst development in cyanobacteria via continuous culture by regulating the levels of combined N or nitrate alone. [ 8 , 27 , 28 , 29 ]. Enhanced development of heterocyst and nitrogenase activity under low levels of combined N or nitrate alone indicated that N fixation by heterocystous cyanobacteria was critical when available N source was limited or absent.…”
Section: Introductionmentioning
confidence: 99%
“…Dolichospermum dominated usually under low N and high P conditions [33] and, in some cases, was enhanced by high P supply [8]. Dolichospermum could excrete alkaline phosphatase when experiencing P de ciency [34]. However, Dolichospermum had no advantage on competing the limited P with Microcystis.…”
Section: Discussionmentioning
confidence: 99%
“…The active and inactive cells with fluorescence were recorded in each image to quantify the percentages of cells with ELF labeling. were harvested in the exponential growth period by centrifugation (3000 rpm, 10 min), rinsed 3 times with P-free BG11 medium and then cultivated in P-free BG11 medium for 48 h to consume P stored in cells to a low level and equal basis [16]. After that, the culture was inoculated in BG11 [17] medium with modified P concentrations and the modifying sets were as follows:…”
Section: Field Sample Collection and Analysismentioning
confidence: 99%